2020
DOI: 10.1038/s41598-020-59188-9
|View full text |Cite
|
Sign up to set email alerts
|

Restricted immunological and cellular pathways are shared by murine models of chronic alcohol consumption

Abstract: Murine models of chronic alcohol consumption are frequently used to investigate alcoholic liver injury and define new therapeutic targets. Lieber-DeCarli diet (LD) and Meadows-Cook diet (MC) are the most accepted models of chronic alcohol consumption. It is unclear how similar these models are at the cellular, immunologic, and transcriptome levels. We investigated the common and specific pathways of LD and MC models. Livers from LD and MC mice were subjected to histologic changes, hepatic leukocyte population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 70 publications
(70 reference statements)
1
22
1
Order By: Relevance
“…
The histological phenotype in LD exposed mice with or without alcohol showed more steatosis than MC mice [2,3]. This is expected considering the liquid high fat diet in LD.
…”
supporting
confidence: 51%
See 2 more Smart Citations
“…
The histological phenotype in LD exposed mice with or without alcohol showed more steatosis than MC mice [2,3]. This is expected considering the liquid high fat diet in LD.
…”
supporting
confidence: 51%
“…Although none of the animal models available reproduce all main aspects of human ALD, they still provide very useful tools to study and understand the molecular mechanisms of the human counterpart [2]. There are two well accepted and commonly used murine models of chronic alcohol consumption introduced by Meadows-Cook (MC) and Lieber-DeCarli (LD) [2,3]. In the MC model, alcohol is introduced in drinking water, in a final concentration increased gradually to reach 20% in most cases [2,4].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…We chose MC, not Lieber DeCarli (LD), the most common mouse model of chronic alcoholic liver injury, because we are interested in studying the specific effect of alcohol on immune cells without the interference of the high fat and liquid diet used in LD model. Moreover, previous work published by our group demonstrated that LD model shared with alcohol exposure alone only a very restricted number of altered pathways (24).…”
Section: Consumption Of Alcohol Resulted In An Increase In Recruited Monocytes/ Macrophages In the Livers Of Female Micementioning
confidence: 84%
“…To investigate the effect of alcohol consumption on monocytes homeostasis, female and male mice received alcohol in drinking water per Meadows-Cook (MC) model, a well-accepted mouse model of chronic alcohol consumption to characterize immunological effects of alcohol (23,24). We chose MC, not Lieber DeCarli (LD), the most common mouse model of chronic alcoholic liver injury, because we are interested in studying the specific effect of alcohol on immune cells without the interference of the high fat and liquid diet used in LD model.…”
Section: Consumption Of Alcohol Resulted In An Increase In Recruited Monocytes/ Macrophages In the Livers Of Female Micementioning
confidence: 99%